2020
DOI: 10.1080/26395940.2020.1829992
|View full text |Cite
|
Sign up to set email alerts
|

A review on occurrence and analytical procedures for the evaluation of polychlorinated naphthalenes in human and environmental matrices

Abstract: Polychlorinated naphthalenes (PCNs) are organochlorine compounds comprising the naphthalene ring system, in which one to eight hydrogen atoms have been substituted with chlorine atoms, yielding 75 chlorinated congeners. They were considered as persistent organic pollutants in May 2015 at the Stockholm Convention owing to their toxicity, persistence, bioaccumulation and potential for long-range transport in the environment. PCNs were invented in the early 1900s to be applied as flame-retardants in consumer prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 118 publications
0
11
0
Order By: Relevance
“…The congener patterns of predominant PCNs in our sediment samples were similar to those observed in marine biota. Reported data showed that highly toxic congeners of PCNs (CNs 66, 67, and 73) are prevalent in marine fish and mammals (e.g., polar bears) across the globe (Bidleman et al, 2010;Agunbiade et al, 2020). This similarity of congener patterns for PCNs in marine sediment and biota could be based on their persistence and bioaccumulation potentials.…”
Section: Congener-specific Profiles and Potential Sources Of Polychlorinated Naphthalenesmentioning
confidence: 99%
See 2 more Smart Citations
“…The congener patterns of predominant PCNs in our sediment samples were similar to those observed in marine biota. Reported data showed that highly toxic congeners of PCNs (CNs 66, 67, and 73) are prevalent in marine fish and mammals (e.g., polar bears) across the globe (Bidleman et al, 2010;Agunbiade et al, 2020). This similarity of congener patterns for PCNs in marine sediment and biota could be based on their persistence and bioaccumulation potentials.…”
Section: Congener-specific Profiles and Potential Sources Of Polychlorinated Naphthalenesmentioning
confidence: 99%
“…In particular, the sediment from Station D2 showed the highest PCN concentration (21,000 pg/g dry wt) in all sediment samples. During the smelting processes of iron and non-ferrous materials (e.g., copper and aluminum), cutting oils could contain PCNs as impurities (Agunbiade et al, 2020;Shen et al, 2021).…”
Section: Spatial Distribution Of Polychlorinated Naphthalenes In Sedimentary Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 To date, PCNs have been detected in various abiotic environmental matrices, including air, water, and soil, as well as in biological matrices, including plants, animals, and humans. 5,6 Furthermore, PCNs exhibit dioxin-like toxicities, such as dermal lesions, endocrine disruption, hepatotoxicity, immunotoxicity, embryotoxicity, teratogenicity, and carcinogenicity. 7−10 Given the potential threats of PCNs to biological health, their bioaccumulation and biomagnification behaviors are of particular concern.…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated naphthalenes (PCNs), which are chlorinated aromatic hydrocarbons with a naphthalene skeleton, comprise 75 congeners from mono-to octa-CN depending on the number and position of the chlorine atoms. Beginning in the 1970s, PCNs were produced for use as ame retardants in electrical devices, waterproo ng materials for wood, paper, and textiles (Agunbiade et al, 2020). The representative technical mixtures of PCNs in industrial markets are Halowax, Seekay, Wako-PCN, and Clonacire waxes (Falandysz et al, 2006(Falandysz et al, , 2008(Falandysz et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%